Pesticides in the Cerrado: social and environmental impacts and popular resistance: Pesticides in the Cerrado: social and environmental impacts and popular resistance (Élisée - Revista de Geografia da UEG, 2020)
The model of agriculture represented by the agribusiness paradigm had as one of the main test fields the Brazilian Cerrado. In this territory, since the middle of the 20th century, this model have been based on the degradation of natural assets and expropriation/violence against the peoples of the Cerrado who, in turn, struggle to maintain their territories and ways of life. In this text, we intends to understand the socio-environmental effects of pesticides and the resistance of traditional populations in the territorial cutting of the Cerrado.
Keywords: Indigenous People. Traditional communities. Quilombolas. Agribusiness